Effect of growth conditions on ?-glucosidase production by local isolate of Aspergillus niger using rice bran substrate - Sri Sugiwati; Muhammad Hanafi; Hanifah Lioe; Maggy Suhartono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sugiwati S, Hanafi M, Lioe HN, Suhartono MT. 2020.  Effect of growth conditions on ?-glucosidase production by local isolate of Aspergillus niger using rice bran substrate. Biodiversitas 21: 4058-4066. ?-Glucosidase is the family of glycosyl hydrolase that have potential role in various food industry, such as in tea, wine and vanilla industries to increase the aroma and production of isoflavone aglycons in soybean flour. The present work produced ?-glucosidase from local isolate of Aspergillus niger InaCC F57 under solid-state fermentation (SSF) using rice bran substrate. Fermentation process was made in various conditions with respect to carbon source as substrate, initial pH of fermentation medium, incubation time, water to substrate ratio, fermentation temperature, and addition of Mandels mineral salts solution. The results showed that activity of ?-glucosidase was best at, i.e., 2.45 U/mL, with the use of rice bran as substrate. Furthermore, optimum condition for the highest production of ?-glucosidase occurred at pH 2.0, incubation time of 5 days, water to substrate ratio of 1.5: 1, and incubation temperature of 32°C. Additionally, in optimum fermentation conditions, production of ?-glucosidase could be enhanced up to 26.22% with the presence of Mandels mineral salts solution as compared to the control.